The Ecolexicons of Cepuk Cloth - Ni Made Ayu Widiastuti; Yana Qomariana; I Wayan Simpen (e-Journal of Linguistics, 2025)
Cepuk cloth has been produced since the 1920s in Tanglad Village, Nusa Penida District, Klungkung Regency, Bali and it has a distinctive motif, different from other clothes produced in the other regencies in Bali. This study tries to identify the lexicons related to cepuk cloth found in the previous research since there have been several research reports on cepuk cloth from 1925. Besides, it also aims to describe the relation between the lexicon and its culture. The data were taken from the previous research concerning cepuk cloth, and they were collected through the observation and documentation methods. The collected data were analyzed qualitatively and the analysis is presented using both formal and informal methods. The results show that there are 66 lexicons related to cepuk cloth categorized into eight, namely characteristic, use, type, motif/pattern, ideology, natural coloring resource, concept of color, and traditional weaving machine. Most of the lexicons are related to flora. There are five categories i.e. cepuk characteristics, uses, motif/pattern, ideology, and color concept that are closely related to Balinese Hindu culture. The lexicons related to culture show the symbolic ecology that investigates the coexistence of languages as symbol systems in Nusa Penida, and the sociocultural ecology that sees language as its part where it then shapes societies and cultures.